FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK - Yuliawati Yuliawati; Paulina Sutrisno (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study aims to obtain empirical evidence regarding business strategy, deferred tax expense and company characteristics such as audit committees, proportion of independent commissioners, institutional ownership, firm size on tax avoidance. These factors were retested because there were still inconsistent results from previous studies and there were variables that were rarely studied. This study uses a sample that includes 396 non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2016 to 2018 period, which is the period surrounding the tax amnesty policy in Indonesia. This study uses the cash effective tax rate (CETR) which is considered as a measure that can describe the amount of tax avoidance by the company. The research hypotheses were tested using multiple linear regression analysis. The results of this study indicate that business strategy have a positive effect on tax avoidance and firm size has a negative effect on tax avoidance, while deferred tax expense, audit committee, proportion of independent commissioners, institutional ownership have no effect on tax avoidance. The theoretical contribution of this study is to add to the development of previous literature related to the effect of business strategy, deferred tax expense and company characteristics such as audit committees, proportion of independent commissioners, institutional ownership, firm size on tax avoidance.